Genetic differentiation among species of the genus Thermophis Malnate (Serpentes, Colubridae) and comments on T. shangrila - Hofmann, Sylvia; Tillack, Frank; Miehe, Georg (Zootaxa, 2015)
The genus Thermophis includes the two species, T. baileyi and T. zhaoermii, which differ morphologically, geographically and molecularly. Recently, a third Thermophis species was described from Shangri-La, northern Yunnan Province, China, and named T. shangrila. The new species was based on morphological and genetic data derived from three specimens. However, the morphological features used to delimit this species seem vague, because they may fall within the range of intraspecific variation of T. zhaoermii. Furthermore, the reported genetic differences in nuclear data are questionable. They likely resulted from a misinterpretation probably due to alignment/analytical flaws or sample/sequence mix-up. Here, we used partial sequences of three mitochondrial (CO1, ND4, cytb) genes and one nuclear (c-mos) gene to analyse the genetic variation between and within species of Thermophis. We inferred the phylogeny using Bayesian Inference and Maximum Likelihood approaches and present additional morphological data that contribute to the knowledge on intraspecific variation in the genus. Our results indicate lacking robustness in the distinguishing morphological features and in the genetic differentiation of T. shangrila and highlight the need for more detailed morphological and molecular studies from a substantially larger sample.